The antibiofilm effect and mechanism of silver nanowire-modified glass ionomer cement against multi-species oral biofilm - Tiantian Guo; Dai Wang; Sherry Shiqian Gao (BMC Oral Health)
Abstract Background To investigate the antibiofilm effect and mechanism of the silver nanowire (AgNW)-modified glass ionomer cement (GIC) against multi-species oral biofilm, and to examine the mechanical and biochemical properties of this novel GIC material. Methods Conventional GIC was incorporated with different concentrations of AgNW and silver nanoparticles (AgNP). Multi-species biofilms of Streptococcus mutans, Streptococcus sobrinus, Lactobacillus fermentum, and Lactobacillus rhamnosus were cultured for 72 h on GIC specimens. Scanning electron microscopy (SEM) was adopted to examine the accumulation of biofilm on GIC surfaces. A live/dead assay was performed to assess the viability of bacteria. Extracellular polysaccharides (EPS) were labelled with Alexa Fluor 647-labelled dextran conjugate and then observed by a confocal laser scanning microscope (CLSM). The D/L-Lactic Acid Assay Kit was used to evaluate the lactic acid production of the multi-species biofilms. Compressive strength, surface roughness, hardness, and wettability were measured by a universal testing machine, an atomic force microscope (AFM), a Vickers microhardness tester, and a contact angle meter, respectively. Colour stability and fluoride release of GIC specimens were assessed by VITA Easyshade® V and ion chromatography. Cell counting kit-8 (CCK-8) was used to study cytotoxicity. Results SEM images showed that fewer biofilms were accumulated on the AgNW-GIC surfaces. The live/dead assay showed that the ratio of live bacteria was significantly lower in AgNW-GIC groups than in conventional GIC (5.8% vs. 100%, p < 0.0001). The EPS production was significantly less in AgNW-GIC groups compared to conventional GIC (p < 0.0001). There is no difference between groups regarding lactic acid production and fluoride release. The mechanical strength including compressive strength, surface roughness, hardness, and wettability were comparable between groups. The colour change between AgNW-GIC and conventional GIC was much milder than that between AgNP-GIC and conventional GIC. The results of cytotoxicity showed no significant differences in cell viability between groups. Conclusions This study demonstrated that AgNW-GIC had an excellent antibiofilm effect against multi-species oral biofilm, comparable mechanical and biochemical properties, and did not significantly affect the colour stability of GIC. The antibiofilm mechanism of AgNW-GIC may be related to inhibiting the viability and EPS production of bacteria.